Partisan competition authorities, Cournot-oligopoly, and endogenous market structure - Laszlo Goerke (Southern Economic Journal, 2022)
The so-called excess-entry theorem establishes conditions guaranteeing that more firms enter a homogeneous Cournot-oligopoly in equilibrium than a benevolent government prefers. We generalize the approach and analyze the behavior of a competition authority, which attaches different weights to the firms' and consumers' payoffs, with welfare-maximization constituting a special case. The greater the importance of consumers, the less likely entry restrictions are, whereas a greater relevance of firms makes a monopoly more probable. The nature of entry restrictions also depends on the competition authority's instruments. The essential insights continue to apply if firms are heterogeneous concerning costs and the timing of output choices.
Keywords: 330; competition authority; Cournot-oligopoly; excessive entry; monopoly; partisan objective